Effect of silica nanoparticles on mechanical and thermal properties of intra-inter ply hybrid laminated composites - Bharathi M; S Senthil Kumaran; P Edwin Samson (Materials Research Express, 2021)
Emissions coming out from the automobile accounts for significant universal carbon emission. The reduction in the weight of the vehicle even by a kilogram can lead to a significant reduction in the carbon emissions, the use of natural fibre composites reduces the weight of the vehicle to a larger extent and minimises the problems associated with the disposal of the vehicle after its service life. The main objective of the work is to develop a light weight, comparatively eco-friendly natural fibre hybrid composite reinforced with intraply carbon +E-glass plies and unidirectional sunn hemp mat interplies and nano silica particles and to evaluate its mechanical and thermal properties for possible application in automobiles. The addition of nano silica was varied between 1wt % to 4 wt %. Mechanical properties investigation through (tensile and impact tests) and thermo mechanical investigation through dynamic mechanical analysis (DMA) and heat deflection temperature (HDT) were carried out. Activation energy of the nano composites was determined using Arrhenius model. Failure analysis of the composites was carried out with field emission scanning electron microscopy (FESEM). Mechanical and thermal properties was found to be higher for the intra-interply polymer composite reinforced with carbon+E-glass fibres and unidirectional sunn hemp mats with 3 wt %. nano silica particles addition. The results obtained in this work will be useful in designing comparatively environmentally friendlier composite structures